Meropenem pharmacokinetics in children: series of cases - Geisa Cristina da Silva Alves; Farah Maria Drumond Chequer; Cristina Sanches (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2018)
Daily doses of antibiotics recommended for children are based on studies in healthy adult volunteers, so this study aimed to describe the pharmacokinetic/pharmacodynamic characteristics of meropenem in children and to verify whether plasma concentrations were within the range therapy. This is a series of cases, which included 4 children, aged 02-12 years old using meropenem dose empirical, 8/8h in 75% of children. The study was conducted in a pediatric hospital from March 2016 to March 2017. Only one child had the result of the culture of biological material recorded in medical records at the time of collection. We observed high inter-patient variability of pharmacokinetic parameters, however plasma concentrations of meropenem were effective in 100% of the study population considering the parameter 40%f T>CIM to CIM of  0.25μg/mL.